Consumption Choices and Earnings Expectations: Empirical Evidence and Structural Estimation - Christian Stoltenberg; Arne Uhlendorff (Tinbergen Institute, 2023)
In this paper, we document that households' consumption expenditures crucially depend on their expected earnings – even after controlling for realized earnings, wealth and time-invariant unobserved characteristics such as permanent income and over-confidence. To explain this evidence, we develop and structurally estimate a standard-incomplete markets model in which rational households receive private signals on their future earnings. We find that households' earnings uncertainty is significantly lower than what is typically assumed in incomplete markets models. Facing lower earnings uncertainty, households prefer less progressive earnings taxes.
Keywords: E21; D31; D84; D52; 330; Private information; household consumption; earnings dynamics; incomplete markets; subjective expectations.